Malformin C preferentially kills glioblastoma stem-like cells via concerted induction of proteotoxic stress and autophagic flux blockade - Phillips, Emma; van Enk, Sizèd; Kildgaard, Sara; Schlue, Silja; Göttmann, Mona; Jennings, Victoria; Bethke, Frederic; Müller, Gabriele; Herold-Mende, Christel; Pastor-Flores, Daniel; Schneider, Martin; Helm, Dominic; et al. (Molecular oncology, 2024)
Glioblastoma is a highly aggressive brain tumor for which there is no cure. The dire prognosis of this disease is largely attributable to a high level of heterogeneity, including the presence of a subpopulation of tumor-initiating glioblastoma stem-like cells (GSCs), which are refractory to chemo- and radiotherapy. Here, in an unbiased marine-derived fungal extract screen, together with bioguided dereplication based on high-resolution mass spectrometry, we identified malformin C to preferentially induce cell death in patient-derived GSCs and explore the potential of this cyclic peptide as a therapeutic agent for glioblastoma. Malformin C significantly reduced tumor growth in an in vivo xenograft model of glioblastoma. Using transcriptomics and chemoproteomics, we found that malformin C binds to many proteins, leading to their aggregation, and rapidly induces the unfolded protein response, including autophagy, in GSCs. Crucially, chemical inhibition of translation using cycloheximide rescued malformin C-induced cell death in GSCs, demonstrating that the proteotoxic effect of the compound is necessary for its cytotoxicity. At the same time, malformin C appears to accumulate in lysosomes, disrupting autophagic flux, and driving cells to death. Supporting this, malformin C synergizes with chloroquine, an inhibitor of autophagy. Strikingly, we observed that autophagic flux is differentially regulated in GSCs compared with normal astrocytes. The sensitivity of GSCs to malformin C highlights the relevance of proteostasis and autophagy as a therapeutic vulnerability in glioblastoma.
Gesehen am 29.04.2025